2014
DOI: 10.1109/tnsre.2014.2312270
|View full text |Cite
|
Sign up to set email alerts
|

Is Sensorimotor BCI Performance Influenced Differently by Mono, Stereo, or 3-D Auditory Feedback?

Abstract: Imagination of movement can be used as a control method for a brain-computer interface (BCI) allowing communication for the physically impaired. Visual feedback within such a closed loop system excludes those with visual problems and hence there is a need for alternative sensory feedback pathways. In the context of substituting the visual channel for the auditory channel, this study aims to add to the limited evidence that it is possible to substitute visual feedback for its auditory equivalent and assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The feedback certainly is the aspect of training protocols for which the most alternatives have been tested. Indeed, the bar representing the classifier output has been replaced by smileys [25] to increase motivation, or by auditory [13,16,30,39] or tactile [9,10,20,21,24] feedback in order to reduce cognitive workload related to the overtaxed visual channel. While auditory feedback seems to be the best solution for Locked-In patients, tactile feedback appeared to be at least as efficient as visual feedback, and more efficient in interactive contexts [20].…”
Section: Mi-bci Training Protocolsmentioning
confidence: 99%
“…The feedback certainly is the aspect of training protocols for which the most alternatives have been tested. Indeed, the bar representing the classifier output has been replaced by smileys [25] to increase motivation, or by auditory [13,16,30,39] or tactile [9,10,20,21,24] feedback in order to reduce cognitive workload related to the overtaxed visual channel. While auditory feedback seems to be the best solution for Locked-In patients, tactile feedback appeared to be at least as efficient as visual feedback, and more efficient in interactive contexts [20].…”
Section: Mi-bci Training Protocolsmentioning
confidence: 99%
“…Giving haptic feedback either leads to comparable results as visual feedback [4] or leads to higher performances [5]. Using the auditory modality for feedback does not seem to be as promising, the performances are either comparable to visual feedback [6] or lower [7]. Regarding the 978-1-4799-8697-2/15/$31.00 c 2015 European Union motivational aspect of feedback several studies have shown that virtual reality feedback was more motivating than the classical bar feedback, and could lead to a higher performance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the form of the feedback, beyond visual feedback, broadly depicted in the review of Alkoby et al (2017), other sensory modalities may be relevant. First, auditory feedback has been used for BCI training (Hinterberger et al, 2004;Gargiulo et al, 2012;McCraedie et al, 2014) and has been experimentally proved to be as effective as visual feedback despite being slower (Nijboer et al, 2008). Second, tactile feedback has also been tested and shown to be comparable to visual feedback for motor-imagery based BCIs (Kauhanen et al, 2006;Cincotti et al, 2007;Chatterjee et al, 2007;Leeb et al, 2013).…”
Section: Adapting the Feedbackmentioning
confidence: 99%